Does Risk Taking Behavior Drive MSME Innovation During Covid-19 Pandemic? - Memarista, Gesti; Wijaya, Olivia; Cahyadi, Tiffany; Afandi, Melissa (Matrik : Jurnal Manajemen, Strategi Bisnis, dan Kewirausahaan; Volume 16 Nomor 1 Tahun 2022, 2022)
The study will contribute to the understanding of risk-taking behavior effect on the MSMEs innovation since the risk-taking behavior is the tendency of business owners for engaging in decisions that may have the potential to be dangerous to their business, especially for the family business to do some innovations nowadays, in the pandemic Covid-19 era. For the family business, the appropriate level of return that the business owner will obtain compensates their risk-taking behavior. These researchers used samples that consist of 307 MSMEs owners that categorized as the family business in Indonesia as the respondents by distributing online questionnaires. Furthermore, this paper also used control variables, such as the number of family members involved, generation level, founder-CEO duality, and business capital. This study used binary logistic regression for the analytical model. The results show that the business owner's risk-taking behavior, number of family members involved, generation level, founder-CEO duality, and business capital significantly influence MSMEs innovation in Indonesia.